A phosphatidylinositol 3-kinase inhibitor strongly suppressed pulmonary vascular remodeling of allergic vasculitis in a murine model. (15th March 2016) - Oikawa, Yuka; Sasaki, Nobuhito; Niisato, Miyuki; Nakamura, Yutaka; Yamauchi, Kohei
ABSTRACT: Objectives: We investigated the effects of pan-class I PI3K inhibitor, ZSTK474 on vascular remodeling using a murine model of allergic vasculitis with eosinophil infiltration.Methods: C57BL/6 mice were sensitized with OVA. The positive controls were exposed to aerosolized OVA daily for 7 days. The other group of mice were administered ZSTK474 (30 mg/kg, p.o. daily) in parallel with daily exposure to aerosolized OVA for 7 days. On the 3rd and 7th day, bronchoalveolar lavage (BAL) was performed and the lungs were excised for pathological analysis. Cell differentials were determined and the concentrations of IL-4, IL-5, IL-13 and TGF-βin BAL fluid were measured.Results: The total cell numbers and eosinophil numbers in BALF were greatly reduced in the ZSTK474-treated group on the 3rd and 7th day after exposure to OVA. The numbers of total white blood cells and eosinophils in the peripheral blood were significantly reduced in the ZSTK474-treated group on the 3rd and 7th day after exposure to OVA. The concentrations of IL-4, IL-5, and IL-13 in BAL fluids were also reduced significantly on the 3rd day in the ZSTK474-treated group. The concentrations of TGF-β in BAL fluids were also reduced significantly on the 3rd and 7th day in the ZSTK474-treated group. The pathological scores reduced significantly in the ZSTK474-treated group compared to the control group.Conclusion: The PI3K inhibitor, ZSTK474 suppressed pulmonary vascular remodeling in the murine model of allergic vasculitis with eosinophil infiltration. PI3K signal transduction may have a critical role in the immunological process that induces allergic vasculitis.